Stochastic Approach of Voltage Optimization to Maximize Power Saving in a Building - Aainaa Mohd Arriffin; Muhammad Murtadha Othman; Amirul Asyraf Mohd Kamaruzaman; Ismail Musirin; Ainor Yahya; Mohd Fuad Abdul Latip (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the energy saving analysis by using voltage optimization technique, via Stochastic approach in an unbalanced three phase building distribution system. The voltage optimization technique is performed by installing voltage regulator units connected in series with every incoming transformer with optimize tap setting, via Stochastic approach using MATLAB® and SIMULINK® software. The results show a substantial improvement in terms of overall cost of energy consumption compared to the base case.